2
$\begingroup$

I want to calculate $E_t[(X_T-K)^+]$ where $$dX_t=\frac{3}{X_t}dt+2X_t dW_t$$ and $X_0=x$. I don't know how extact the strong solution of this SDE. Indeed I used Ito's lemma but it was not usefule.

Thanks for attantion.

$\endgroup$
2
$\begingroup$

Note that \begin{align*} d\left(X_t^2\right) &= 2X_t dX_t + d\langle X, X\rangle_t\\ &=(6+4X_t^2)dt + 4X_t^2dW_t, \end{align*} which can be solved using the technique with an integral factor. Specifically, note that \begin{align*} d\left(e^{4t-4W_t}X_t^2 \right) &= X_t^2 d\left(e^{4t-4W_t}\right) + e^{4t-4W_t} d(X_t^2) + \left\langle d\left(e^{4t-4W_t}\right), d(X_t^2) \right\rangle\\ &=e^{4t-4W_t}X_t^2(12dt-4dW_t)\\ &\quad +e^{4t-4W_t}\left[(6+4X_t^2)dt + 4X_t^2dW_t\right]- 16 e^{4t-4W_t}X_t^2 dt\\ &=6e^{4t-4W_t} dt. \end{align*} Then \begin{align*} e^{4t-4W_t}X_t^2 &= x^2+6\int_0^t e^{4s-4W_s} ds. \end{align*} That is, \begin{align*} X_t^2 = e^{4W_t-4t}\left(x^2+6\int_0^t e^{4s-4W_s} ds \right). \end{align*}

A general note. For an equation of the form \begin{align*} dY_t = (aY_t+b)dt + (cY_t+d) dW_t, \end{align*} we can apply an integral factor of the form $$e^{(-a+\frac{1}{2}c^2)t -cW_t}.$$

$\endgroup$
  • $\begingroup$ Thanks. Why should we use dynamic of $X_t^2$ instead of dynamic of $X_t^3$ or $X_t^4$? $\endgroup$ – Crisis2008 Nov 2 '16 at 18:43
  • $\begingroup$ That is based on the structure of your equation. With $X_t^2$, you can have an equation that have coefficients as linear functions of $X_t^2$. For $X_t^3$ and $X_t^4$, they do not have such nice property. The equation for $X_t^2$ does not come up arbitrarily: if you multiply $X_t$ to both sides of your equation, you instantly see the relationship with $X_t^2$. $\endgroup$ – Gordon Nov 2 '16 at 18:49
  • $\begingroup$ How should we know it? $\endgroup$ – Crisis2008 Nov 2 '16 at 18:57
  • $\begingroup$ This equation $X_tdX_t = 3dt +2 X_t^2 dW_t$ is the same as your original equation. Do you see the relationship with $X_t^2$? You may need a relatively good sense in mathematics. $\endgroup$ – Gordon Nov 2 '16 at 19:01
3
$\begingroup$

You shouldn't say: "Ito's lemma wasn't useful". Set $$Y_t=-2W_t+2t\tag 1$$ Note $W_0=0$ thus $Y_0=0$.We have $$dY_t=2\,dt-2\,dW_t\tag 2$$ Set $Z_t=e^{Y_t}$. By application of Ito's lemma, we have $$dZ_t=e^{Y_t}\,dY_t+\frac{1}{2}e^{Y_t}d[Y_t,Y_t]\tag 3$$ therefore $$dZ_t=4e^{Y_t}dt-2\,e^{Y_t}dW_t=4Z_tdt-2Z_tdW_t\tag 4$$ on the other hand $$d(X_t\,Z_t)=Z_t\,dX_t+X_t\,dZ_t+d[X_t,Z_t]\tag 5$$ thus $$d(X_t\,Z_t)=\frac{3Z_t}{X_t}dt\tag 6$$ in other words $$d(X_t\,Z_t)=\frac{3Z_t^2}{X_tZ_t}dt\tag 7$$ set $R_t=X_tZ_t$. We have $$dR_t=\frac{3Z_t^2}{R_t}dt\tag 8$$ This can be solved as a regular ODE with separable variables : $$R_t\,dR_t=3Z_t^2\, dt$$ and $$\frac{1}{2}R_t^2-\frac{1}{2}R_0^2=3\int_0^{t}Z_s^2ds\\ \frac{1}{2}R_t^2-\frac{1}{2}x^2=3\int_0^{t}Z_s^2ds\tag 9$$ then $$X_t^2=e^{-2Y_t}\left(x^2+6\int_0^{t}e^{2Y_s}ds\right)\tag {10}$$ Finally

$$\color{red}{X_t^2=e^{4W_t-4t}\left(x^2+6\int_0^{t}e^{-4W_s+4s}ds\right)\tag{11}}$$

Now How can you calculate $\mathbb{E}_t[(X_T-K)^+]?$

$\endgroup$
  • $\begingroup$ Sorry Gordon's solution is easier than yours. $\endgroup$ – Crisis2008 Nov 2 '16 at 20:04
  • $\begingroup$ No problem --:) $\endgroup$ – user16651 Nov 2 '16 at 20:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.